Analysis of the Integration of Design within the MSMEs of Zone 9 of the DM of Quito -Ecuador that Generate Products with Added Value for export - Bravo, Dely N. (2022)
Well-managed design favors the growth of the company since it brings the product closer to the final consumer and provides economic and social benefits for the company; however, in spite of being an activity recognized by many SMEs worldwide, in Ecuador there is a lack of knowledge about what design really is, means and contributes. This article analyzes the perspective of manufacturing MSMEs in Zone 9 of the Metropolitan District of Quito on design and their level of integration, in order to determine the contribution of the application of design in the development of value-added products for export.